FILM FINANCING AND THE DIGITAL MARKET: FUTURE, THE ROLE IN INDIA WITH AND MODELS OF FINANCING - Oak, Amit Padmakar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Film financing has undergone a revolutionary transformation in the digital age, introducing innovative methods to fund, distribute, and monetize films. This paper examines the role of digital markets in reshaping the financing and economic models of the Indian film industry. By exploring crowdfunding, digital rights sales, and streaming platforms, it evaluates how technological advancements have impacted the accessibility and sustainability of film financing. The study also identifies challenges, such as intellectual property protection, and assesses the potential of hybrid models in promoting inclusive and profitable filmmaking.